Availability of Information and Communication Technology Resources for Enhancing Teachers' Instructional Delivery in Private Secondary Schools in Port-Harcourt Metropolis - Hillary Wordu; Mercy Jaja; Tamunokubie Gideon (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2022)
The study investigated the availability of ICT resources for enhancing teachers' Instructional delivery in Private Secondary Schools in Port-Harcourt Metropolis. The purpose of the study was to investigate the availability, adequacy and utilization of ICT resources for enhancing teachers’ instructional delivery in the schools. The descriptive survey design was adopted for the study. The population for the study consisted of all private secondary school teachers in Port-Harcourt Metropolis. Multistage sampling technique was used to select the sample. To achieve this, 10 Private Secondary Schools were selected from each of the two Local Government Areas in Port Harcourt Metropolis. From each of the 10 schools, 160 teachers (80 males and 8o females) were randomly sampled. A self-structured checklist/questionnaire was used as an instrument to collect data for the study. Cronbach Alpha reliability was used to establish the internal consistency of the instrument which yielded 0.86, 0.85 and 0.77 reliability indexes. The data collected were analyzed using percentages, mean and standard deviation while z-test was used to test the hypothesis at 0.05 level of significant. The findings of this study show that laptop computers, printers, Internet facilities, PowerPoint projectors, radio and television sets, educational software amongst others were ICT resources available for enhancing teachers’ instructional delivery in private secondary schools. Secondly, the findings showed that computer printers, Radio and television sets, smart phones among others are adequate for teachers’ instructional delivery in private secondary school. The study also found that computers and laptops, internet facilities, educational software amongst others are utilized for instructional delivery to a high extent. It was therefore recommended that private schools administration should scale up the provision of ICT resources for instructional delivery. In addition, teachers' skills in the utilization of ICT resources should be improved.